2020
DOI: 10.1002/ecy.3205
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence history increases ecosystem stability and resilience in experimental plant communities

Abstract: Understanding factors that maintain ecosystem stability is critical in the face of environmental change. Experiments simulating species loss from grassland have shown that losing biodiversity decreases ecosystem stability. However, as the originally sown experimental communities with reduced biodiversity develop, plant evolutionary processes or the assembly of interacting soil organisms may allow ecosystems to increase stability over time. We explored such effects in a long‐term grassland biodiversity experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 81 publications
10
42
1
Order By: Relevance
“…Here, we found that 4 years of soil microbial community re-assembly under identical plant species compositions was not enough to remove the strong soil legacy effect that had developed under these same plant species compositions for 8 years previous to the experiment. The differences between soil treatments were even maintained through a severe natural flood at the field site in spring 2013 (van Moorsel et al, 2020); during which the plots were completely submerged by standing water. We found much faster adjustments of rhizosphere microbiomes in an associated experiment with the same soil legacy from the Jena Experiment (M.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we found that 4 years of soil microbial community re-assembly under identical plant species compositions was not enough to remove the strong soil legacy effect that had developed under these same plant species compositions for 8 years previous to the experiment. The differences between soil treatments were even maintained through a severe natural flood at the field site in spring 2013 (van Moorsel et al, 2020); during which the plots were completely submerged by standing water. We found much faster adjustments of rhizosphere microbiomes in an associated experiment with the same soil legacy from the Jena Experiment (M.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the strong effects of soil legacy on soil microbial communities, effects of plant community history were much weaker. This was unexpected because those same plant community history treatments led to significant plant evolutionary responses, including changes in plant–plant interactions (Zuppinger-Dingley et al, 2014; van Moorsel et al, 2018 and 2020) and even altered plant–soil feedbacks (Hahl et al, 2020; Zuppinger-Dingley et al, 2016). These evolutionary changes in the plant communities may have been too small to become influential on the diversity and composition of soil microbial communities that may need more time to develop or are too subtle to detect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme climatic events such as droughts are predicted to be more frequent in the future 1,2 , with potentially negative effects on the functioning of ecosystems and the provision of ecosystem services for human well-being [3][4][5][6][7] . Ecosystems may adjust to climatic extremes by changes in species abundances [8][9][10] or evolutionary responses of populations [11][12][13][14][15][16][17][18][19] . Both experimental and observational studies have shown that higher biodiversity buffers temporal variation in ecosystem functioning against extreme climatic events 20-24 .…”
Section: Main Textmentioning
confidence: 99%
“…We used the biomass difference between 2-species mixtures vs. monocultures to calculate the net biodiversity effects, which we further partitioned into complementarity effects (indicating niche differentiation or facilitation) and sampling effects (indicating a disproportionate contribution to community productivity of one or the two species; which is also referred as "selection effect" elsewhere, a term we did not use in this study to avoid confusion) 48 . Second, we assessed the effects of drought selection on resistance (biomass ratio during vs. before the drought), recovery (biomass ratio after vs. during the drought) and resilience (biomass ratio after vs. before the drought) of productivity 19,20 . Third, we tested whether altered plant interactions drove the above differences between the two selection treatments.…”
mentioning
confidence: 99%